Review Metode Deposisi Elektrokimia Cu2ZnSnS4 sebagai Lapisan Absorber Sel Surya Lapisan Tipis - Hanifa, Husna; Prima, Eka Cahya; Suhendi, Endi (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2024)
Cu2ZnSnS4 is a low-cost and environmentally friendly thin layer solar cell absorber material. The electrochemical deposition method is intended to study because it enables producing films with high homogeneity based on solution precursors. This research review focuses on examining the CZTS electrochemical deposition method in order to identify the effect of the sulfurization process (sulfurization temperature and time) so that the best electrochemical deposition process can be identified for future work of high-efficiency CZTS thin layer solar cell fabrication based on solution precursor. The results show that the Cu2ZnSnS4 layer deposited through the electrochemical method has a 1.4-1.6 eV bandgap range. The etching process to post-annealing 0.1M KCN is crucial to effectively and selectively remove CuS, ZnS, and Cu6Sn5 secondary phases.